BENEFITS OF AUTOGENIC TRAINING THERAPY FOR TEENAGERS: A SYSTEMATIC REVIEW (Jurnal Ipteks Terapan, 2023)
Introduction: Autogenic Training (AT) is a relaxation technique which is a structured process of automatic suggestion like self-hypnosis. This activity can be used to reduce several complaints, both physical and psychological. The purpose of writing this article is to find out the benefits of autogenic training in teenagers. Method: Systematic review of articles from nine databases, namely ClinicalKey, EBSCOhost, EMBASE, ProQuest, ScienceDirect, Scopus, Oxford Journals, Pubmed and Google Scholar . Article searches were carried out using the keywords Autogenic Training, Autogenic Relaxation, Child, Adolescent and were limited to the years 1992-2022. Results: From the results of the data base search, 8,105 articles were identified, of which there were 10 articles that were relevant for systematic review. Autogenic training is able to reduce pain in adolescents, especially in cases of migraines, other headaches and dysmenorrhea. In addition, this intervention can be used to reduce behavioral and emotional disorders such as anxiety and stress. Autogenic training can also be used to control self-control or self-regulation. Conclusion: Autogenic training provides many benefits for teenagers, such as reducing pain, anxiety and stress responses, increasing attention, increasing the ability to control emotional regulation or self-control and maintaining a good mood